Adjustment to Equilibrium after a Demand Shock: A Strategic Interaction View - Luca Lambertini; Luigi Marattin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
In this paper we verify the functioning of the standard neoclassical adjustment to equilibrium after a demand shock in a non-cooperative simultaneous Cournot duopoly with complete, symmetric and imperfect information. Our results show that in such a framework the adjustment to the long-run level of output by the entire industry or part of it is no longer guaranteed. We show that the size of the demand shock determines the nature and number of equilibria generated by strategic interaction, whereas the post-adjustment real wage level determines which equilibrium is actually obtained.
Keywords: D43; E30; 330